2016
DOI: 10.1177/1934578x1601100915
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Configuration and Body Part Distribution of the Alkaloid 6-epi-Monanchorin from the Marine Polychaete Chaetopterus variopedatus

Abstract: As a result of the first study on secondary metabolites from the cosmopolitan bioluminescent marine tube polychaete Chaetopterus variopedatus, a new bicyclic guanidine alkaloid, 6-epi-monanchorin (1), along with the previously known monanchorin (2) were isolated. The structure of 1 was elucidated by spectroscopic and chemical methods, including a cleavage of the C 1-O 7 bond to obtain a secondary alcohol (3), which was used to determine the absolute configurations by Mosher's method. It was found that 1 and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The 6- epi -monanchorin ( 2 , Figure 1) was isolated from the EtOAc extracts of both cells and lyophilized culture broth using reverse-phase HPLC. The structure was exactly identified on the basis of 1 H NMR and HRESIMS data by comparison with authentic sample [4]. As a result, it was found that the CB1-14 strain biosynthesizes 6- epi -monanchorin ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 6- epi -monanchorin ( 2 , Figure 1) was isolated from the EtOAc extracts of both cells and lyophilized culture broth using reverse-phase HPLC. The structure was exactly identified on the basis of 1 H NMR and HRESIMS data by comparison with authentic sample [4]. As a result, it was found that the CB1-14 strain biosynthesizes 6- epi -monanchorin ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the marine guanidine alkaloids found in marine sponges are polycyclic, and two bicyclic representatives of this group, namely monanchorin ( 1 ) and 6- epi -monanchorin ( 2 ), are known. These compounds were isolated from representatives of two phylogenetically distant taxa, namely marine sponges Monanchora ungiculata and Halichondria panicea (phylum Porifera) [2,3], and marine polychaete Chaetopterus variopedatus (phylum Annelida) [4]. Previously it has been reported that the compound 1 shows weak cytotoxic activity against IC2 murine mast cells [2], while compounds 1 and 2 (Figure 1) are able to inhibit the migration and colony formation of cisplatin-resistant cancer NCCIT-R cells [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent application of Mosher’s procedure resulted in the esters 180a , b , which allowed determination of the absolute configurations of all of the stereogenic centers of 178 (Scheme ). The same configurations with the exception of the C-6 stereogenic center had earlier been established in the related monanchorin and confirmed by stereoselective syntheses. , …”
Section: Hydrogenolysismentioning
confidence: 99%